The first trial of CIM331, a humanized antihuman interleukin‐31 receptor A antibody, in healthy volunteers and patients with atopic dermatitis to evaluate safety, tolerability and pharmacokinetics of a single dose in a randomized, double‐blind, placebo‐controlled study. (1st February 2016) - Nemoto, O.; Furue, M.; Nakagawa, H.; Shiramoto, M.; Hanada, R.; Matsuki, S.; Imayama, S.; Kato, M.; Hasebe, I.; Taira, K.; Yamamoto, M.; Mihara, R.; et al.
Summary: Background: The cytokine interleukin‐31 (IL‐31) is considered to be responsible for the development of pruritus in humans. At present, no available evidence has been provided on the safety and efficacy of blocking the IL‐31 signal in humans for the amelioration of pruritus in atopic dermatitis (AD). CIM331 is a humanized antihuman IL‐31 receptor A (IL‐31RA) monoclonal antibody, which binds to IL‐31RA to inhibit subsequent IL‐31 signalling. Objectives: To assess the tolerability, safety, pharmacokinetics and preliminary efficacy of CIM331 in healthy Japanese and white volunteers, and Japanese patients with AD. Methods: In this randomized, double‐blind, placebo‐controlled phase I/Ib study, CIM331 was administered in a single subcutaneous dose. The primary outcomes were safety and tolerability; the exploratory analysis was efficacy. Results: No deaths, serious adverse events (AEs) or discontinuations due to AEs were reported in any part of the study. No dose‐dependent increase in the incidence of AEs occurred in any part of the study. In healthy volunteers, all AEs occurred once in the placebo groups, and increased creatine phosphokinase was more common in the CIM331 groups. In patients with AD, CIM331 reduced pruritus visual analogue scale score to about −50% at week 4 with CIM331 compared with −20% with placebo. CIM331 increased sleep efficiency and decreased the use of hydrocortisone butyrate. Conclusions: A single subcutaneous administration of CIM331 was well tolerated in healthy volunteers and patients with AD. It decreased pruritus, sleep disturbance and topical use of hydrocortisone. CIM331 may become a novel therapeutic option for AD by inhibiting IL‐31.